(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The article discusses the issues of training specialists in accounting in the specialty "Finance and Credit". Young specialists now live in an environment where knowledge of certain areas becomes an asset of the future. After all, the transformation that young people are currently going through can be compared with the speed of sound, and the main and their task is to adapt to a new reality and a new course of life. The purpose of this article is to present the features of training specialists in accounting in the banking sector. Particular attention is paid to the analysis of the qualification requirements of the employer in the employment of accounting specialists in the banking sector, as well as the attitude of students to the profession of accountant. As a result of the analysis of job search sites, it was concluded that the practical part of the training of such specialists should be aimed at adapting students to practice from the very first year. In any case, continuous monitoring of the labor market in the banking sector should be carried out due to its volatility. After that, changes must be made to the main educational program. The article has been prepared on the basis of the current regulatory and legislative framework of the Russian Federation, recommendations are given on the organization of education